High Glucose Suppresses Epidermal Growth Factor Receptor/Phosphatidylinositol 3-Kinase/Akt Signaling Pathway and Attenuates Corneal Epithelial Wound Healing - Xu, Ke-Ping; Li, Yanfeng; Ljubimov, Alexander V.; Yu, Fu-Shin X. (Diabetes (New York, N.Y.), 2009)
High Glucose Suppresses Epidermal Growth Factor Receptor/Phosphatidylinositol 3-Kinase/Akt Signaling Pathway and Attenuates Corneal Epithelial Wound Healing Ke-Ping Xu 1 , Yanfeng Li 1 , Alexander V. Ljubimov 2 and Fu-Shin X. Yu 1 1 Kresge Eye Institute, Departments of Ophthalmology and Anatomy and Cell Biology, Wayne State University School of Medicine, Detroit, Michigan; 2 Ophthalmology Research Laboratories, Cedars-Sinai Medical Center, Los Angeles, California. Corresponding author: Fu-Shin X. Yu, fyuatmed.wayne.edu . Abstract OBJECTIVE Patients with diabetes are at an increased risk for developing corneal complications and delayed wound healing. This study investigated the effects of high glucose on epidermal growth factor receptor (EGFR) signaling and on epithelial wound healing in the cornea. RESEARCH DESIGN AND METHODS Effects of high glucose on wound healing and on EGFR signaling were investigated in cultured porcine corneas, human corneal epithelial cells, and human corneas using Western blotting and immunofluorescence. Effects of high glucose on reactive oxygen species (ROS) and glutathione levels and on EGFR pathways were assessed in porcine and primary human corneal epithelial cells, respectively. The effects of EGFR ligands and antioxidants on high glucose–delayed epithelial wound healing were assessed in cultured porcine corneas. RESULTS High glucose impaired ex vivo epithelial wound healing and disturbed cell responses and EGFR signaling to wounding. High glucose suppressed Akt phosphorylation in an ROS-sensitive manner and decreased intracellular glutathione in cultured porcine corneas. Exposure to high glucose for 24 h resulted in an increase in ROS-positive cells in primary human corneal epithelial cells. Whereas heparin-binding EGF-like growth factor and antioxidant N-acetylcysteine had beneficial effects on epithelial wound closure, their combination significantly accelerated high glucose–delayed wound healing to a level similar to that seen in control subjects. Finally, Akt signaling pathway was perturbed in the epithelia of human diabetic corneas, but not in the corneas of nondiabetic, age-matched donors. CONCLUSIONS High glucose, likely through ROS, impairs the EGFR–phosphatidylinositol 3-kinase/Akt pathway, resulting in delayed corneal epithelial wound healing. Antioxidants in combination with EGFR ligands may be promising potential therapeutics for diabetic keratopathy. Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Received July 23, 2008. Accepted January 20, 2009. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. © 2009 by the American Diabetes Association.